A Multi-criteria assessment of energy crops for biogas production - Vindiš, Peter (Strojniški vestnik, 2010)
This paper presents the system for the assessment of energy crops for biogas production. The system is based on simulation modelling and multi criteria decision analysis. The deterministic simulation system consists of deterministic production simulation models that enable different types of costs calculations for the production of energy crops, electrical and heat energy in biogas production. Simulation model results were further evaluated using a qualitative multi-attribute modelling methodology (supported by the software tool DEX-i) and quantitative analytical hierarchical process - APH (supported by software toll Expert Choice 2000). The Analysis showed that by using current model the most relevant alternative used for energy crop for biogas production is maize. The maize results in the best multicriteria evaluation EC=0.248 and DEX-i evaluation = appropriate. the best alternative for maize is sorghum with multicriteria evaluation of EC=0.201 and DEX-i evaluation = less appropriate.
Keywords: bioplin; energetske rastline; energija; simulation modeli; večkriterijska analiza